Diagnostic Algorithm for Joint Pain in Patients with Inflammatory Bowel Disorders - A. I. Dolgushina; G. M. Khusainova; O. B. Nesmeyanova; N. V. Kirsh; O. V. Solovieva; E. A. Bogdanova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim. An algorithm development for joint pain differential diagnosis in patients with inflammatory bowel disorders (IBD) and its validation in clinical practice.Materials and methods. A total of 349 IBD patients hospitalised for gastroenterological complaints at the Chelyabinsk Regional Clinical Hospital during 2017–2020 have been examined.Results. Upon survey, 97 (27.8%) IBD patients complained of joint pain. Ulcerative colitis (UC) predominated (79 patients; 81.4%), Crohn’s disease (CD) had a 18.6% incidence. In survey, 27% UC and 32.1% CD patients reported joint pain (p = 0.26). Among IBD patients, 52.6% had mechanical, and 47.4% — inflammatory pain. The inflammatory back pain (IBP) rate in survey cohort was 23.7%. Use of a diagnostic algorithm allowed concomitant rheumatic disease detection in 7 (7.2%) patients from the IBD–joint pain cohort: 2 patients were diagnosed with psoriatic spondyloarthritis, 2 — rheumatoid arthritis, 1 — gout and 2 — with ankylosing spondylitis. IBD-associated arthritis was diagnosed in 41 (42.3%) cases, osteoarthritis — in 38 (39.2%) IBD patients with joint pain, arthralgia with no objective inflammation, impaired joint function or lesions in X-ray and/or ultrasound — in 13 (13.4%) patients.Conclusion. Joint pain complaints are common in IBD patients and require a multispecialty rheumatologists-involving approach to proceed with differential diagnosis and opting for treatment tactics. A clinically verified algorithm coupled with laboratory tests and instrumental imaging facilitates diagnosis and optimal therapy selection in IBD patients with complaints of joint pain.